Mean and fluctuating basal forces generated by granular flows: Laboratory observations in a large vertically rotating drum. Issue 6 (11th June 2014) - Hsu, L.; Dietrich, W. E.; Sklar, L. S.
Abstract A flowing granular mass generates forces on the boundary that drive near‐bed grain dynamics, bed surface erosion, and energy dissipation. Few quantitative analyses exist of the controls on the dynamically fluctuating force caused by granular flows with wide‐grain‐size distributions and a liquid phase in the pores. To study the mechanisms controlling the boundary forces, we used a 225 cm2 load plate to measure the bed‐normal force from a suite of granular flows in a 4 m diameter, 80 cm wide vertically rotating drum. We analyzed the time series of bed forces generated in flows composed of granular material for both narrow (gravel‐water) and wide (muddy, sand‐gravel‐cobble) grain‐size distributions. The tail of the force distribution was captured more closely by a generalized Pareto distribution than an exponential distribution, suggesting a way to predict empirically the force distribution. We show that the impulse on the bed, related to kinetic energy transferred to the bed from the granular collisions, is quantified by the standard deviation of the force. The mean bulk force equaled the static weight of the flow, whereas the force fluctuations, represented by the standard deviation and the averaged top 1% of force, were a near‐linear function of effective grain diameter and flow velocity, and a ∼0.5 power function of an inertial stress scaling term. The force fluctuations depend on both Savage and Bagnold numbers. The correlations revealed in this study suggest that it may be possible to estimate dynamic forces on the bed from gross properties of the flows.